Time course of recovery of vertical jump height and heart rate versus running speed after a 90-km foot race - Chamberts, C.; Noakes, T. D.; Lambert, E. V.; Lambert, M. I. (Journal of Sports Sciences, 1998)
The aim of this study was to characterize the time course of recovery of muscle function and the heart rate response to steady-state exercise following an ultramarathon. Eight male runners (46 # 7 years; mean # s) competing in the 90-km Comrades marathon and seven control runners (45 # 6 years) with the same running experience (11 # 3 years), but who did not run in the race, were recruited for the study. The heart rate response to various running speeds on the track was measured twice before the race. Squat jump, counter-movement jump and drop jump height were measured on three occasions before the race. The track tests were repeated on days 4, 11, 18, 25 and 32 after the race. The vertical jump tests were repeated on the day of the race and on days 1, 2, 3, 4, 5, 11, 18, 25 and 32 after the race. Although the heart rate response to steady-state exercise was elevated at all speeds (3.75–4.55 m&12;#&12;s −1) for the duration of the study, this difference was only statistically significant on day 25 after the race (P < 0.05). Vertical jump height was significantly reduced in the experimental group immediately after the race ( P < 0.00001), as was the squat jump for up to 18 days ( P < 0.001) after the race. Actual height jumped in the squat jump was reduced by as much as 20 cm immediately after the race. Leg extensor muscle power, as measured by vertical jump height, is impaired in runners for up to 18 days after a 90-km ultramarathon. Furthermore, runners have a delayed exaggerated heart rate response to steady-state running at moderate to high intensities up to 25 days after an ultra-endurance event.